Impact of Covid-19 on GDP and Trade: A Case of African Countries - Talla M. Al-Deehani (Arthatama: Journal of Business Management and Accounting, 2020)
This research aims to find out the impact of Covid-19 on the GDP and Trade of African countries. This research paper has employed a quantitative design to determine the relationship between Covid-19 and the GDP and Trade of African counties. This research has analyzed the historic data from 1961 to 2020 to study the differences in the economic growth caused due to the pandemic. Stata hasbeen used for analyzing the data where descriptive statistics and Panel data regression have been applied. In particular, the GLS model has been applied due to heteroscedasticity in the variables. The quantitative data of the study that was collected for this research has shown that Covid-19 has negatively influenced the economic performance and productivity of African countries. The ten Africancountries selected for this research were influenced adversely in the context of trading activities and GDP growth.